Non-diffraction propagation of acoustic waves in a rapidly modulated stratified medium - Xing-Feng Zhu (Nature Portfolio, 2017)
Abstract A rapidly modulated stratified medium with a large mass density modulation depth (LMMD) is proposed to achieve non-diffraction propagation (NDP) of acoustic waves. It is found that the NDP in LMMD medium is independent of the incident angle and can be operated in a broad-band manner. Such an NDP is robust and is unhampered by medium losses. An effective medium theory (EMT) is developed for acoustic waves propagating in the LMMD medium based on the first-principles method. The LMMD EMT is verified by using the transfer-matrix method (TMM) for both propagating and evanescent waves. Furthermore, we discuss the influence of the geometry on NDP, and finite element simulations are conducted to verify the NDP in the LMMD medium.